2003
DOI: 10.1017/s0144686x03001211
|View full text |Cite
|
Sign up to set email alerts
|

Care-giver network transformations: the need for an integrated perspective

Abstract: This paper reviews recent research on care-giver networks and the concepts and approach that they apply, with particular reference to the support networks of the primary care-givers of older people with Alzheimer's disease. It makes the case for an integrated approach to the explanation of the various combinations of formal and informal support that are found. It argues that more attention needs to be given to transformations in care-giver networks over time, and that this will require more development of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 54 publications
1
67
0
Order By: Relevance
“…First, we performed categorical content analysis (Miles & Huberman, 1994) and focused on two elements related to family history: family members 'health status and actors' caregiving experiences. We also explored the concept of linked lives by identifying actors both through the network approach (second section of the questionnaire) and through our narrative analysis (third section; Carpentier & Ducharme, 2003. The combined findings of the social network approach and narrative methodology are illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First, we performed categorical content analysis (Miles & Huberman, 1994) and focused on two elements related to family history: family members 'health status and actors' caregiving experiences. We also explored the concept of linked lives by identifying actors both through the network approach (second section of the questionnaire) and through our narrative analysis (third section; Carpentier & Ducharme, 2003. The combined findings of the social network approach and narrative methodology are illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two main models of the relationship between formal and informal care have been defined: a complementary taskspecific model (Carpentier and Ducharme 2003) in which formal care emerges when a dependent person's needs exceed informal caregiver capacities; and a supplementary or substitution model, where formal and informal caregivers provide similar types of care, and are therefore replaceable (Davey and Patsios 1999). The study by Bonsang (2009) of Europe using data from SHARE 2004 found that informal care is an effective substitute for formal care as long as the needs of the dependent older adults are low and require unskilled care.…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed the new concept of carer network which is based on the relationships in an existing healthcare regime that is common worldwide [44]. The carer network, works in harmony with, and provides support for, existing relationships and interactions between patients and healthcare professionals: 1) the doctor or consultant in charge of the management of the healthcare regime; 2) the professional carer who is a local contact for the patient and implements the clinical care (e.g.…”
Section: B Carer Networkmentioning
confidence: 99%